Quantitative approach for reclassification of the spatial cluster of archipelagos in Maluku Province for the basis of forest development - Patrich Papilaya; Endang Suhendang; I Nengah Surati Jaya; Teddy Rusolono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
In natural resource management, it is necessary to group regions based on the similarity of their spatial and non-spatial characteristics, to efficiency and effectiveness Therefore, this study describes the re-grouping of the twelve island clusters established by the provincial government of Maluku into more homogeneous classes. The re-grouping was carried out based on the biophysical conditions of the regions, therefore, it could be used as the basis for determining the forest management units. The results showed that the twelve designated island clusters could be simplified to eight more homogeneous island clusters with 86.4% accuracy and 82.2 validation. It also showed that there were thirteen significant changes in the grouping of clusters of the island, including the horticultural crop area (Bf) and horticultural crop production (E). Moreover, when the island cluster is reclassified into 5 classes, the grouping would be more accurate, with 94.9% accuracy and 92.4% validation. This study concludes that there are two dominant factors in the classification of the island cluster in Maluku province namely, biophysical and social.